Magnesium alloy surface treatment liquid for new energy automobile and preparation method of magnesium alloy surface treatment liquid
By combining zeolite imidazole ester skeleton structure materials and other additives in the surface treatment liquid of magnesium alloy for new energy vehicles, the problem of poor corrosion resistance and wear resistance of magnesium alloy is solved, and it has significantly improved its in new energy vehicles Application performance in .
Patent Information
- Application Number
- CN202411335052.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
The corrosion resistance and wear resistance of magnesium alloys for new energy vehicles are poor, which limits their application in the automotive field, and the demand for wear resistance is more stringent during dynamic use.
Develop a surface treatment liquid for magnesium alloy for new energy vehicles, including zeolite imidazole skeleton structure material (ZIF-67), reduced graphene oxide, nanowires, dispersants, citric acid, benzotriazole, cerium corrosion inhibitor, Nanosols, polyvinyl alcohol and epoxy resins form coatings through specific mixing and stirring steps to improve the corrosion and wear resistance of magnesium alloys.
This surface treatment liquid effectively improves the corrosion resistance and wear resistance of magnesium alloys, extends its service life, and is suitable for automotive magnesium alloys of different brands, achieving high corrosion resistance, high wear resistance and high impact resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal material surface treatment, and in particular to a magnesium alloy surface treatment liquid for new energy vehicles and a preparation method thereof. Background Art
[0002] Under the general background of energy conservation and emission reduction, intelligence and lightweight have become the main trends in the automotive industry. In the process of lightweighting of automobiles, magnesium alloys have become the most promising structural materials in the automotive field due to their low density, high specific strength, good forming performance, heat dissipation performance, shock absorption performance and electromagnetic shielding performance. For traditional fuel vehicles, the main purpose of lightweight technology application is to reduce fuel consumption and reduce emission pollution; while for new energy vehicles, lightweight technology can help improve the cruising range and meet the core needs of customers. The rapid development of the new energy vehicle industry in recent years will bring about a continuous growth in the demand for magnesium alloys. Based on the four major systems of the whole vehicle, AZ91D, AM60B, AM50 and AS41 B magnesium alloys have become the most commonly used grades of magnesium alloys for automobiles.
[0003] However, some inherent characteristics of magnesium alloys have also hindered their application in the automotive field. Magnesium and its alloys are very active in chemical properties and are easily oxidized and corroded in the air. In addition, magnesium alloys have low hardness and poor wear resistance. The use of automobiles is a dynamic process, and the requirements for wear resistance are more stringent. In order to overcome the poor corrosion resistance and wear resistance of magnesium alloys and extend the service life of automotive magnesium alloys, surface treatment is an effective means.
[0004] In the prior art, common magnesium alloy surface treatment methods include anodizing, micro-arc oxidation, electrochemical plating, spraying, etc., which have high requirements on equipment and complex operations; while treating magnesium alloy with surface treatment liquid is relatively simple to operate and easy to mass produce.
[0005] Based on this, it is of great significance to develop a surface treatment liquid that can improve the corrosion resistance and wear resistance of magnesium alloys for new energy vehicles. Summary of the invention
[0006] The present invention provides a magnesium alloy surface treatment liquid for new energy vehicles and a preparation method thereof, which solves the problem of poor corrosion resistance and wear resistance of magnesium alloys for new energy vehicles in the related art.
[0007] The technical solution of the present invention is as follows:
[0008] In a first aspect, the present invention discloses a magnesium alloy surface treatment liquid for new energy vehicles, comprising the following raw materials in parts by weight:
[0009] 10-15 parts of zeolite imidazolate framework structure material (ZIF-67, hereinafter referred to as such), 3-6 parts of reduced graphene oxide, 4-8 parts of nanowires, 1-3 parts of dispersant, 3-7 parts of citric acid, 8-14 parts of benzotriazole, 5-10 parts of cerium corrosion inhibitor, 6-9 parts of nanosol, 4-7 parts of polyvinyl alcohol, 2-4 parts of epoxy resin, and 100 parts of deionized water;
[0010] Furthermore, the preparation method of ZIF-67 is:
[0011] Cobalt nitrate hexahydrate and 2-methylimidazole are dissolved in the same volume of methanol solution to form cobalt nitrate hexahydrate methanol solution and 2-methylimidazole methanol solution, and then the cobalt nitrate hexahydrate methanol solution is added to the 2-methylimidazole methanol solution, and the mixture is stirred at 25-35° C. and 500-600 r / min for reaction for 12-18 hours. After the reaction is completed, the precipitate is collected by centrifugation, and the precipitate is dried at 60° C. for 6-8 hours to obtain ZIF-67.
[0012] Furthermore, the solid-liquid ratio of the cobalt nitrate hexahydrate methanol solution is (3-5) g:100 mL, and the solid-liquid ratio of the 2-methylimidazole methanol solution is (4-5.5) g:100 mL.
[0013] Furthermore, the reduced graphene oxide has a sheet diameter of 0.5-10 um.
[0014] Furthermore, the nanowires are one or a mixture of silicon dioxide nanowires with a particle size of 30-60 nm or silicon carbide nanowires with a particle size of 10-30 nm.
[0015] Furthermore, the dispersant is any one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, or a mixture of any two thereof.
[0016] Furthermore, the cerium corrosion inhibitor is any one of cerium chloride, cerium nitrate, and cerium phosphate, or a mixture of any two thereof.
[0017] Furthermore, the nanosol is any one of titanium dioxide nanosol with a particle size of 5-10 nm and aluminum oxide nanosol with a particle size of 10-15 nm, or a mixture of the two.
[0018] In a second aspect, the present invention further discloses a method for preparing the magnesium alloy surface treatment liquid for new energy vehicles as described above, characterized in that it comprises the following steps:
[0019] S1, weigh each raw material by weight;
[0020] S2. Add ZIF-67 and reduced graphene oxide to deionized water, stir at 30-50°C for 35-45 minutes with ultrasonic stirring, and then stir at 800-1000 r / min for 1-2 hours; then add nanowires and dispersant and stir at ultrasonic stirring for 40-60 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue stirring at 800-1000 r / min for 3-5 hours to form a mixture;
[0021] S3. Add nanosol and polyvinyl alcohol to the mixture, heat it to 95-105°C, and stir it at 300-500r / min for 30-60min; cool it to 30-50°C, add epoxy resin, and continue stirring for 2-3h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0022] The working principle and beneficial effects of the present invention are:
[0023] (1) The magnesium alloy surface treatment liquid for new energy vehicles of the present invention comprises ZIF-67, reduced graphene oxide, nanowires, dispersant, citric acid, benzotriazole, cerium corrosion inhibitor, nanosol, polyvinyl alcohol, epoxy resin, and deionized water; the surface treatment liquid can form a coating on the surface of the magnesium alloy, and the preparation method is simple and suitable for mass production.
[0024] (2) The magnesium alloy surface treatment liquid for new energy vehicles of the present invention utilizes ZIF-67 and reduced graphene oxide as composite nanocontainers, which can effectively load corrosion-inhibiting components. The organic skeleton structure of ZIF-67 can hinder the penetration of corrosive media. The high hardness and good lubrication effect of reduced graphene oxide sheets can achieve the wear resistance of magnesium alloys for vehicles.
[0025] (3) The magnesium alloy surface treatment liquid for new energy vehicles of the present invention improves the surface hardness of the magnesium alloy by adding nanowires, thereby improving the wear resistance and impact resistance of the magnesium alloy; and improves the corrosion resistance of the coating through the multiple effects of citric acid, benzotriazole, and cerium corrosion inhibitor.
[0026] (4) The nanosol, polyvinyl alcohol and epoxy resin added to the magnesium alloy surface treatment liquid for new energy vehicles of the present invention have the function of sealing the nanocontainer on the one hand, thereby maximizing the anti-corrosion ability of the magnesium alloy; secondly, the adhesion effect of the nanosol and epoxy resin and the cross-linking effect of polyvinyl alcohol are conducive to the formation of a densified coating with excellent bonding strength, thereby jointly improving the wear resistance and impact resistance of the magnesium alloy after treatment. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0029] Example 1
[0030] Preparation of ZI F-67;
[0031] 4 g of cobalt nitrate hexahydrate and 4.8 g of 2-methylimidazole were respectively dissolved in 100 mL of methanol solution to form cobalt nitrate hexahydrate methanol solution and 2-methylimidazole methanol solution, and then the cobalt nitrate hexahydrate methanol solution was slowly added to the 2-methylimidazole methanol solution, and the mixture was stirred at 600 r / min at 30°C for 15 h. After the reaction was completed, the precipitate was collected by centrifugation and dried in an oven at 60°C for 8 h to obtain ZIF-67.
[0032] Example 2
[0033] Preparation of magnesium alloy surface treatment solution;
[0034] Step 1: Weigh each raw material by weight, as shown in Table 1 below:
[0035] Table 1
[0036]
[0037]
[0038] Step 2: Add ZIF-67 and reduced graphene oxide to deionized water, stir at 40°C for 40 minutes and then at 900 r / min for 1.5 hours; then add nanowires and dispersant, stir at 900 r / min for 50 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue to stir at 900 r / min for 4 hours to form a mixture;
[0039] Step 3: Add nanosol and polyvinyl alcohol to the mixture, heat to 100°C, and stir at 400r / min for 45min; add epoxy resin after cooling to 40°C, and continue stirring for 2.5h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0040] Example 3
[0041] Preparation of magnesium alloy surface treatment solution;
[0042] Step 1: Weigh each raw material by weight, as shown in Table 2 below:
[0043] Table 2
[0044]
[0045]
[0046] Step 2: Add ZIF-67 and reduced graphene oxide to deionized water, stir at 50°C for 45 minutes and then at 1000 r / min for 2 hours; then add nanowires and dispersant, stir at 1000 r / min for 60 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue to stir at 1000 r / min for 4 hours to form a mixture;
[0047] Step 3: Add nanosol and polyvinyl alcohol to the mixture, heat to 105°C, and stir at 500r / min for 60min; add epoxy resin after cooling to 50°C, and continue stirring for 3h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0048] Example 4
[0049] Preparation of magnesium alloy surface treatment solution;
[0050] Step 1: Weigh each raw material by weight, as shown in Table 3 below:
[0051] Table 3
[0052]
[0053] Step 2: Add ZIF-67 and reduced graphene oxide to deionized water, stir at 30°C for 35 minutes and then at 800 r / min for 1 hour; then add nanowires and dispersant, stir at 800 r / min for 40 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue to stir at 800 r / min for 3 hours to form a mixture;
[0054] Step 3: Add nanosol and polyvinyl alcohol to the mixture, heat to 95°C, and stir at 300r / min for 30min; add epoxy resin after cooling to 30°C, and continue stirring for 2h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0055] Example 5
[0056] Preparation of magnesium alloy surface treatment solution;
[0057] Step 1: Weigh each raw material by weight, as shown in Table 4 below:
[0058] Table 4
[0059]
[0060] Step 2: Add ZIF-67 and reduced graphene oxide to deionized water, stir at 45°C for 40 minutes and then at 950 r / min for 1.5 hours; then add nanowires and dispersant, stir at 950 r / min for 55 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue to stir at 950 r / min for 4.5 hours to form a mixture;
[0061] Step 3: Add nanosol and polyvinyl alcohol to the mixture, heat to 102°C, and stir at 430r / min for 50min; add epoxy resin after cooling to 45°C, and continue stirring for 2.5h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0062] Example 6
[0063] Preparation of magnesium alloy surface treatment solution;
[0064] Step 1: Weigh each raw material by weight, as shown in Table 5 below:
[0065] Table 5
[0066] raw material Composition and origin Weight ZIF-67 Prepared from Example 1 11 Reduced graphene oxide Self-purchase 3.5 Nanowires Self-purchased silica nanowires (particle size 30-60nm) 5 Dispersants Sodium dodecyl sulfate 2 Citric Acid Self-purchase 4 Benzotriazole Self-purchase 9 Cerium Corrosion Inhibitor Cerium chloride purchased from 6 Nanosol Self-purchased titanium dioxide nanosol (particle size 5-10nm) 7.5 Polyvinyl alcohol Self-purchase 5 Epoxy resin Self-purchase 3 Deionized water self made 100
[0067] Step 2: Add ZIF-67 and reduced graphene oxide to deionized water, stir at 35°C for 38 minutes and then at 850 r / min for 1.5 hours; then add nanowires and dispersant, stir at 850 r / min for 45 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue to stir at 850 r / min for 3.5 hours to form a mixture;
[0068] Step 3: Add nanosol and polyvinyl alcohol to the mixture, heat to 98°C, and stir at 350r / min for 40min; add epoxy resin after cooling to 35°C, and continue stirring for 2h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
[0069] Comparative Example 1
[0070] A blank control was used, i.e. no magnesium alloy surface treatment solution was prepared.
[0071] Comparative Example 2
[0072] Preparation of magnesium alloy surface treatment solution;
[0073] The preparation method is different from that of Example 2 only in that ZI F-67 is not prepared in step 1 and ZI F-67 is not added in step 2, and other conditions are exactly the same, and finally a magnesium alloy surface treatment solution is obtained.
[0074] Comparative Example 3
[0075] Preparation of magnesium alloy surface treatment solution;
[0076] The preparation method is different from that in Example 2 only in that reduced graphene oxide is not prepared in step 1 and reduced graphene oxide is not added in step 2, and other conditions are exactly the same, and finally a magnesium alloy surface treatment solution is obtained.
[0077] Comparative Example 4
[0078] Preparation of magnesium alloy surface treatment solution;
[0079] The preparation method is different from that of Example 2 only in that nanowires are not prepared in step 1 and nanowires are not added in step 2, and other conditions are exactly the same, and a magnesium alloy surface treatment solution is finally obtained.
[0080] Comparative Example 5
[0081] Preparation of magnesium alloy surface treatment solution;
[0082] The preparation method is different from that of Example 2 only in that citric acid is not prepared in step 1 and citric acid is not added in step 2, and other conditions are exactly the same, and a magnesium alloy surface treatment solution is finally obtained.
[0083] Comparative Example 6
[0084] Preparation of magnesium alloy surface treatment solution;
[0085] The preparation method is different from that of Example 2 only in that benzotriazole is not prepared in step 1 and benzotriazole is not added in step 2, and other conditions are exactly the same, and a magnesium alloy surface treatment solution is finally obtained.
[0086] Comparative Example 7
[0087] Preparation of magnesium alloy surface treatment solution;
[0088] The preparation method is different from that of Example 2 only in that no cerium corrosion inhibitor is prepared in step 1 and no cerium corrosion inhibitor is added in step 2, and other conditions are exactly the same, and finally a magnesium alloy surface treatment solution is obtained.
[0089] Comparative Example 8
[0090] Preparation of magnesium alloy surface treatment solution;
[0091] The preparation method is different from that of Example 2 only in that step three is removed, and other conditions are exactly the same, and finally a magnesium alloy surface treatment liquid is obtained.
[0092] Comparative Example 9
[0093] Preparation of magnesium alloy surface treatment solution;
[0094] The preparation method is different from that of Example 2 only in that no nanosol is prepared in step 1 and no nanosol is added in step 3, and other conditions are exactly the same, and finally a magnesium alloy surface treatment solution is obtained.
[0095] Comparative Example 10
[0096] The preparation method is different from that in Example 2 only in that polyvinyl alcohol in step 1 and step 3 is replaced by polyvinyl pyrrolidone, and other conditions are exactly the same, and finally a magnesium alloy surface treatment liquid is obtained.
[0097] Comparative Example 11
[0098] The preparation method is different from that of Example 2 only in that the epoxy resin in step 1 and step 3 is replaced by phenolic resin, and other conditions are exactly the same, and finally a magnesium alloy surface treatment liquid is obtained.
[0099] Test example
[0100] The magnesium alloy surface treatment liquids prepared in Examples 2-6 and Comparative Examples 1-11 were used to perform surface treatment on four commonly used automotive magnesium alloys, AZ91 D, AM60B, AM50A and AS41 B (Comparative Example 1 was not treated). The treatment method was as follows: the magnesium alloy was polished to a bright finish and cleaned with acetone until the surface was clean; then the magnesium alloy sample was immersed in the magnesium alloy surface treatment liquid, stirred at 200 r / min for 30 minutes, then washed with pure water, and then placed in a 90°C drying oven for 1 hour to obtain the magnesium alloy treated with the surface treatment liquid. The performance of the treated automotive magnesium alloy was then tested, and the test method was as follows:
[0101] Corrosion resistance: The samples are subjected to a neutral salt spray test (GB / T 10125-2021). After 1000 hours of testing, if there is no rust on the surface of the sample, it is qualified, otherwise it is unqualified.
[0102] Hardness: The Vickers hardness of the sample surface coating was measured using a micro-Vickers hardness tester.
[0103] Friction resistance: The friction coefficient of the sample coating is calculated through the test ring-test block sliding wear test (GB / T 12444-2006).
[0104] Impact resistance test: refer to GB / T 1732-2020 "Determination of impact resistance of paint film", the weight of the impact tester is 1kg, the experimental height is selected as 50cm, and the coating of the sample is observed for cracks and peeling. If there is no crack or peeling, it is considered qualified, otherwise it is considered unqualified.
[0105] Cupping test: Refer to GB / T 4156-2020 "Erichsen cupping test for metal sheets and strips". The test is carried out using a cupping tester. The specified punching depth is 4mm. When the specified depth is reached, the sample is taken out to observe whether the coating of the sample has cracks or peeling. If there is no crack or peeling, it is considered qualified, otherwise it is considered unqualified.
[0106] The results of the above performance tests are listed in Table 6-7, which is as follows:
[0107] Table 6
[0108]
[0109]
[0110] Table 7
[0111]
[0112]
[0113] By analyzing the test results in Table 6-7, we can conclude that:
[0114] Examples 2, 3, 4, 5, and 6 are performance test results of four commonly used grades of automotive magnesium alloys after surface treatment with the magnesium alloy surface treatment liquid for new energy vehicles prepared under different parameter settings permitted by the present invention. The results show that the magnesium alloy surface treatment liquid for new energy vehicles prepared by the present invention can be applied to different grades of automotive magnesium alloys, and achieves high corrosion resistance, high wear resistance and high impact resistance of the magnesium alloy after treatment.
[0115] By comparing the test results of Comparative Example 1 with those of Example 2, it can be seen that the magnesium alloy surface treatment liquid for new energy vehicles prepared in Example 2 can greatly improve the corrosion resistance and friction resistance of the magnesium alloy for vehicles. The magnesium alloy not treated with the surface treatment liquid fails the salt spray test, has low hardness and poor wear resistance.
[0116] By comparing the test results of Comparative Examples 2 and 3 with Example 2, it can be seen that the ZIF-67 and reduced graphene oxide in the magnesium alloy surface treatment liquid for new energy vehicles prepared in Example 2 can improve the corrosion resistance, wear resistance and impact resistance of the magnesium alloy for vehicles after treatment. This is because ZIF-67 and reduced graphene oxide constitute a composite nanocontainer, which can effectively load corrosion inhibition components and is conducive to the corrosion inhibition effect; and the organic skeleton structure of ZIF-67 can hinder the penetration of corrosive media, and the high hardness and good lubrication effect of the reduced graphene oxide sheet can improve the wear resistance of the magnesium alloy after treatment.
[0117] By comparing the test results of Comparative Example 4 with those of Example 2, it can be seen that the nanowires in the magnesium alloy surface treatment liquid for new energy vehicles prepared in Example 2 can improve the wear resistance and impact resistance of the magnesium alloy for vehicles after treatment, which is attributed to the increase in the hardness of the surface coating of the magnesium alloy after treatment.
[0118] By comparing the test results of Comparative Examples 5, 6, and 7 with those of Example 2, it can be seen that the citric acid, benzotriazole, and cerium corrosion inhibitor in the magnesium alloy surface treatment liquid for new energy vehicles prepared in Example 2 can improve the corrosion resistance of the treated magnesium alloy for vehicles, which is attributed to the synergistic corrosion inhibition effect of citric acid, benzotriazole, and cerium corrosion inhibitor.
[0119] By comparing the test results of Comparative Example 8 with those of Example 2, it can be seen that the addition of nanosol, polyvinyl alcohol and epoxy resin in the magnesium alloy surface treatment liquid for new energy vehicles prepared in Example 2 can improve the corrosion resistance, wear resistance and friction resistance of the magnesium alloy for vehicles after treatment. This is because the nanosol, polyvinyl alcohol and epoxy resin can seal the nanocontainer to prevent the loss of corrosion-resistant components and maximize the anti-corrosion ability of the magnesium alloy; secondly, the adhesion of the nanosol and epoxy resin and the cross-linking effect of polyvinyl alcohol are conducive to the formation of a densified coating with excellent bonding strength, which together improve the wear resistance and impact resistance of the magnesium alloy after treatment.
[0120] From the comparison of the test results of Comparative Examples 9, 10 and 11 with those of Example 2, it can be seen that any component of the nanosol, polyvinyl alcohol and epoxy resin has a significant effect on the corrosion resistance, wear resistance and friction resistance of the treated magnesium alloy.
[0121] In summary, the magnesium alloy surface treatment liquid for new energy vehicles of the present invention can improve the corrosion resistance, friction resistance and impact resistance of magnesium alloy for vehicles.
[0122] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A magnesium alloy surface treatment liquid for new energy vehicles, characterized in that: The invention comprises the following raw materials in parts by weight: 10-15 parts of zeolite imidazolate skeleton structural material, 3-6 parts of reduced graphene oxide, 4-8 parts of nanowires, 1-3 parts of dispersant, 3-7 parts of citric acid, 8-14 parts of benzotriazole, 5-10 parts of cerium corrosion inhibitor, 6-9 parts of nanosol, 4-7 parts of polyvinyl alcohol, 2-4 parts of epoxy resin, and 100 parts of deionized water.
2. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The preparation method of the zeolite imidazolate framework structure material is: Cobalt nitrate hexahydrate and 2-methylimidazole are respectively dissolved in the same volume of methanol solution to form cobalt nitrate hexahydrate methanol solution and 2-methylimidazole methanol solution, and then the cobalt nitrate hexahydrate methanol solution is added to the 2-methylimidazole methanol solution, and the mixture is stirred at 500-600 r / min at 25-35° C. for 12-18 hours. After the reaction is completed, the precipitate is collected by centrifugation, and the precipitate is dried at 60° C. for 6-8 hours to obtain a zeolite imidazole ester framework structure material.
3. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 2, characterized in that: The solid-liquid ratio of the cobalt nitrate hexahydrate methanol solution is (3-5) g:100 mL, and the solid-liquid ratio of the 2-methylimidazole methanol solution is (4-5.5) g:100 mL.
4. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The reduced graphene oxide has a sheet diameter of 0.5-10 um.
5. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The nanowires are one of silicon dioxide nanowires with a particle size of 30-60 nm or silicon carbide nanowires with a particle size of 10-30 nm, or a mixture of the two.
6. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The dispersant is any one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate or a mixture of any two of them.
7. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The cerium corrosion inhibitor is any one of cerium chloride, cerium nitrate, and cerium phosphate, or a mixture of any two of them.
8. The magnesium alloy surface treatment liquid for new energy vehicles according to claim 1, characterized in that: The nano sol is any one of a titanium dioxide nano sol with a particle size of 5-10 nm and an aluminum oxide nano sol with a particle size of 10-15 nm, or a mixture of the two.
9. A method for preparing a magnesium alloy surface treatment liquid for new energy vehicles according to any one of claims 1 to 8, characterized in that: The steps include: S1, weigh each raw material by weight; S2. Add zeolite imidazolate framework material and reduced graphene oxide to deionized water, stir at 30-50°C for 35-45 minutes and then at 800-1000 r / min for 1-2 hours; then add nanowires and dispersant and stir at 800-1000 r / min for 40-60 minutes; then add citric acid, benzotriazole and cerium corrosion inhibitor in sequence, and continue stirring at 800-1000 r / min for 3-5 hours to form a mixture; S3. Add nanosol and polyvinyl alcohol to the mixture, heat it to 95-105°C, and stir it at 300-500r / min for 30-60min; cool it to 30-50°C, add epoxy resin, and continue stirring for 2-3h to obtain the magnesium alloy surface treatment liquid for new energy vehicles.
Citation Information
Patent Citations
Corrosion protection for metallic substrates comprising one or more 2d material platelets
CN112236485A
Preparation method of high-corrosion-resistance modified epoxy resin composite coating
CN112341900A
Metal organic framework / epoxy coating, and preparation method and application thereof
CN113801538A
ZIF / GO-based synergistic corrosion inhibition filler as well as preparation method and application thereof
CN118546554A
Cited By
Environment-friendly neodymium iron boron surface treating agent and preparation method thereof
CN120554873A